Application of heuristic assembly line balancing methods to lighting automation industry - KARATEPE MUMCU, YELDA (My University, 2022)
The assembly line balancing problem is an important issue for every manufacturing company. A balanced assembly line ensures that a product is produced in the optimum time, and as a result of this effect, less machinery, materials and labour are used during this production. In this article, theoretical information about assembly line balancing has been given, and then the data needed for assembly line balancing has been obtained by making a time study of the production of Downlight Luminaire. With these data obtained, assembly line balancing was done and compared by using Hoffman and Comsoal methods. The aim of this study is to investigate the applicability of Hoffman and Comsoal methods, which are one of the heuristic assembly line balancing methods, in the assembly lines of the companies producing in the lighting sector.
Keywords: Elektrik-Elektronik Mühendisliği; Mühendislik ve Teknoloji; Electrical and Electronics Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, ELECTRICAL & ELECTRONIC; Elektrik ve Elektronik Mühendisliği; Sinyal İşleme; Fizik Bilimleri; Electrical and Electronic Engineering; Signal Processing; Physical Sciences; Assembly Line Balancing; Heuristic Assembly Line Balancing; Methods; Hoffman Method; Comsoal Method; Lighting Automation Manufacturing